Optimizing Maintenance Budgets and LED Investment to Improve Power Plant Reliability and Sustainability - Utama, Setya Cahya; Siswanti, Indra (ARE Publisher, 2026)
Objectives: Power plant reliability and sustainability are critical factors in ensuring a stable electricity supply. PLTU Suralaya Units 5–7, one of the largest coal-fired power plants in Indonesia’s Java–Bali system, has experienced increasing operational disturbances and rising maintenance costs due to suboptimal budget allocation. This study aims to analyze strategies to enhance power plant reliability and sustainability through maintenance budget optimization and investment in LED lighting technology. Methodology: This research employs a mixed-method case study approach integrating qualitative and quantitative analyses. Data were obtained from operational reports, maintenance budget records, disturbance logs, and field observations. Analytical tools include SWOT analysis, IFE–EFE matrices, and time series analysis to evaluate performance before and after optimization implementation. Finding: The results indicate that maintenance budget optimization based on asset criticality improves preventive maintenance effectiveness, reduces forced outages, and enhances reliability performance. Additionally, LED lighting investment reduces internal energy consumption, lowers operational costs, and minimizes hazardous waste from conventional lighting systems. Conclusion: This study concludes that integrating maintenance budget optimization with LED investment effectively improves reliability, cost efficiency, and sustainability performance. The findings provide a practical managerial framework for power plant operators seeking to enhance operational performance while supporting sustainability objectives.